The Effect of Due Professional Care and Auditor Integrity on Audit Quality - Rahman, Erpi; Nurmayanti, Santi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Audit quality plays a crucial role in ensuring the reliability, accuracy, and integrity of a company's financial statements, which are essential for stakeholder decision-making. High-quality audits help ensure that financial information is accurate, transparent, and in accordance with applicable standards and regulations. This study aims to examine the effect of professional prudence and auditor integrity on audit quality in Public accounting firms located in Bandung, Indonesia. A quantitative research method was employed, using statistical techniques such as regression, correlation, and hypothesis testing to analyze the data collected. The sample consisted of 36 qualified respondents selected based on specific criteria to ensure the validity of the results. The findings show that both due professional care and auditor integrity significantly impact audit quality, contributing a combined effect of 50.8%. Hypothesis testing results indicate that the t-values for both variables—2.337 for due professional care and 2.312 for auditor integrity—exceed the critical value of 2.035. This confirms that both variables have a statistically significant influence on audit quality and support the research hypothesis.